Lean manufacturing implementation in filling and distribution process in Lactogal, Produtos Alimentares - Cordeiro, Joana Margarida Bento (2020)
Nowadays, the technological evolution is unleashing big changes inside organizations, directly affecting their operational environment. Therefore, these new dynamics have been playing a role to encourage news ways to work. A continuous need to improve processes to earn efficiency and achieve competitive advantage is becoming noticeable worldwide. This report presents a study conducted in a national dairy company, more specifically in the production department, with focus on the organization of the shop floor through an improvement on material flows and a growth in the performance of two similar productive lines. The main objective of the project was to improve material and information flows, as well as a reduction on time and frequency of stops of the two selected productive lines. To do that, process mapping and waste analysis tools were used. While the Lean philosophy was chosen to map the process and the information flows, tools like 5S’s and OEE were used to identify non-value-added activities, and consequently, the wastes in those processes. For prove the concept, different scenarios were tested on the shop floor. As a practical contribution of the project it is expected that these proposed improvements, that combine people, data, flows and processes, will enhance efficiency earnings in the daily activities of the operator, and in the identification and reduction of stops that do not add value, thus improving the global performance of the productive activity.